STUDI MUTU KERUPUK RUMPUT LAUT (Eucheuma spinosum) KAITANNYA TERHADAPSIFAT KIMIAWI DAN ORGANOLEPTIK - Iman Setya Dwi Ardani; Yanuar Rustrianto Buwono (Faculty of Science and Technology University Ibrahimy, 2018)
Currently in Indonesia developed many new products processed from seaweed such as crackers. Seaweed is one of the natural ingredients, grown in Indonesia that can replace harmful materials such as borax. On crackers, adding seaweed gives the advantage of having a distinctive flavor savory, crunchy and also has many health benefits for the human body. The purpose of the study was to find the ratio of starch and seaweed right to produce crude fiber content, water content, crispness, flavor and color of seaweed crackers healthy. The results showed that the ratio of starch and different seaweed significantly affect the level of moisture content, crispness, flavor and color as well as the very significant effect on crude fiber content